Effectiveness of Chemistry Learning Media Development Project in Improving Collaboration - Ekaputra, Firdiawan (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to examine the effectiveness of applying the project-based learning model in the form of developing chemical learning media in improving student collaboration. The sample used was 22 students of Academic Year 2023/2024 who attended the learning multimedia design lecture. The instrument used in this research is a questionnaire sheet for collaboration skills. The technique used to collect data in this study is a student collaboration questionnaire. Collaboration data before and after the application of the project-based learning model was tested for normality before hypothesis testing. The normality test results in this study amounted to 0.121, so the data in this study were normally distributed and could be parametric tested in hypothesis testing. Based on the hypothesis test conducted, a significance value of 0.00 was obtained, so that in this study it can be concluded that there is an effectiveness of the application of the project-based learning model in the form of developing chemical learning media in improving student collaboration. The magnitude of the impact of using the project-based learning model in learning activities, it is hoped that the project-based learning model can continue to be applied in learning to improve student skills and make learning more meaningful.